2014
DOI: 10.1134/s0018151x14040233
|View full text |Cite
|
Sign up to set email alerts
|

Glow discharge in a transverse supersonic gas flow at low pressures

Abstract: A low pressure glow discharge in a transverse supersonic gas flow was experimentally studied for the case where the flow only partially fills the interelectrode gap. It is shown that the space region with super sonic gas flow has a higher concentration of gas particles and, therefore, works as a charged particle generator. The near electrode regions of glow discharge are concentrated specifically in this region. This structure of glow discharge is promising for plasma deposition of coatings under ultralow pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…There is fundamentally new solution to this problem [1,2]. It is creation of zones with different concentrations of neutral particles in electrode gap.…”
Section: Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…There is fundamentally new solution to this problem [1,2]. It is creation of zones with different concentrations of neutral particles in electrode gap.…”
Section: Relevancementioning
confidence: 99%
“…Reaching the stable quality of finished product, its cost is reduced and there is a possibility of its mass implementation. Analysis of technological surface treatment processes showed that control of process parameters and analysis of systems working capacity is difficult due to the of ultrafast processes in high-energy technology complex [1,2]. Maintaining the stability of the process variables is possible due to system response in a short time.…”
Section: Relevancementioning
confidence: 99%
“…An alternative method of solving the problem is to create regions with different concentrations of neutral particles in the interelectrode gap. As it was shown in [4][5], the organization of supersonic gas flow in a limited area of the interelectrode gap makes it possible to control the distribution of discharge parameters between the cathode and the anode. Pumping gas at supersonic speed allows you to create regions with different values of gas concentrations in the interelectrode space and in this way change the distribution of concentrations of electrons and ions, as well as the potential and intensity of the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…The external flow in this case shielded the discharge plasma from the atmosphere. The method of influencing the characteristics of a glow discharge using a supersonic flow was also investigated and developed in [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%